LANGUAGE AND DISCOURSE IN NIGERIAN EDUCATION: HISTORIC IMPLICATION OF GENDER ISSUES - OFFIONG, EKWUTOSI ESSIEN (Society Register, 2019)
Abstract This paper examines the influence and power of language in education in Nigeria from the precolonial to colonial and post-colonial times. This is with regards to the effect of language on gender issues within the country. Nigeria, a country on the west coast of Africa is multi-ethnic with over 150 (one hundred and fifty) ethnic groups with their different indigenous languages and cultures. As a colony of the British, the Christian missionaries who first introduced western form of education in Nigeria used the British English language as a medium of communication and subsequently with the establishment of colonial administration in the country, English language was made the official language of the country. This paper contains a critical analysis of the use of English Language in the country and its implications on communication in social and economic interactions of individuals within the various communities across the country. It argues that the proliferation of the English language was through education of which the male gender benefitted more than their female counterparts due to the patriarchal dominance in the country. The data for the study was collated from random interviews and other written sources. The research discovered that the knowledge and ability to speak fluently and write the English language had a direct influence on the socio-political and economic status of individuals within the country. The women who benefitted from this were comparatively fewer than the men due to some prevailing conditions of what could be called in the present the subjugation of women the society. Critical discourse analysis is adopted for this study. It argues that English language dependency by Nigerians shows that forms of the colonial experience is still evident and these were all initiated during the past interactions with west through the transatlantic slave trade and colonial rule. This is because discourse as a social construct is created and perpetuated by the persons who have the language power and means of communication. The Nigerian family being of a conservative orientation derives its power directly from the father who is the patriarch of the family as obtained in the traditional set up of communities and the Nigerian society in general. This has grave effect on the opposite gender